2017
DOI: 10.1515/forum-2016-0231
|View full text |Cite
|
Sign up to set email alerts
|

Sequential motion planning algorithms in real projective spaces: An approach to their immersion dimension

Abstract: Thes-th higher topological complexity{\operatorname{TC}_{s}(X)}of a spaceXcan be estimated from above by homotopical methods, and from below by homological methods. We give a thorough analysis of the gap between such estimates when{X=\operatorname{\mathbb{R}P}^{m}}, the real projective space of dimensionm. In particular, we describe a number{r(m)}, which depends on the structure of zeros and ones in the binary expansion ofm, and with the property that{0\leq sm-\operatorname{TC}_{s}(\operatorname{\mathbb{R}P}^{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Jesus González ( [2]) has particular interest in estimates for TC k pP 3¨2 e q. We shall prove the interesting fact that our Theorems 1.1 and 1.4 improve significantly on the cohomological lower bound for TC 3 pP 3¨2 e q, but not for TC k pP 3¨2 e q when k ą 3.…”
Section: Numerical Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Jesus González ( [2]) has particular interest in estimates for TC k pP 3¨2 e q. We shall prove the interesting fact that our Theorems 1.1 and 1.4 improve significantly on the cohomological lower bound for TC 3 pP 3¨2 e q, but not for TC k pP 3¨2 e q when k ą 3.…”
Section: Numerical Resultsmentioning
confidence: 79%
“…In this section, we prove Theorems 1.1 and 1.4. The first step, Theorem 2.1, follows suggestions of Jesus González, and is similar to work in [2]. We are very grateful to González for these suggestions.…”
Section: Proofs Of Main Theoremsmentioning
confidence: 75%
See 1 more Smart Citation
“…In this section, we examine some special cases of our results (in Propositions 3.1 and 3.5) and make comparisons with some work in [1]. The numbers z 3 pnq " zcl 3 pP n q are 1 less than a sequence which was listed by the author as A290649 at [3] in August 2017.…”
Section: Examples and Comparisonsmentioning
confidence: 99%
“…In [1,Thm 5.7], it is shown that our g k pnq in Theorem 1.6 is a decreasing function of k, and achieves a stable value of 2 νpn`1q´1 for sufficiently large k. They defined spnq to be the minimal value of k such that g k pnq " 2 νpn`1q´1 . We obtain a formula for the precise value of spnq in our next result.…”
Section: Examples and Comparisonsmentioning
confidence: 99%